2014
DOI: 10.1021/ac404051f
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Pharmaceutical Effect of Drugs on Atherosclerotic Lesions in Vivo Using Integrated Fluorescence Imaging and Raman Spectral Measurements

Abstract: Direct assessment of the vascular lesions of model animals in vivo is important for the development of new antiatherosclerotic drugs. Nevertheless, biochemical analysis of the lipid profile in blood in vitro remains the most common way to evaluate the therapeutic effect of drugs targeting atherosclerosis because of an inherent difficulty to access the vascular wall. Using hypercholesterolemic zebrafish, we present an orchestrated application of Raman spectral measurements and confocal fluorescence imaging to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…RS also allows for one to study the mechanisms of treatment different diseases in vivo and in situ. The effect of two different drugs (ezetimibe and atorvastatin) on atherosclerotic plaques using fluorescent and RM was investigated [225]. The study confirmed the pharmaceutical effect of both drugs and showed that the drug ezetimibe reduces the deposition of lipids in the vascular walls.…”
Section: Rs In Biomedicine and Diagnosticsmentioning
confidence: 79%
“…RS also allows for one to study the mechanisms of treatment different diseases in vivo and in situ. The effect of two different drugs (ezetimibe and atorvastatin) on atherosclerotic plaques using fluorescent and RM was investigated [225]. The study confirmed the pharmaceutical effect of both drugs and showed that the drug ezetimibe reduces the deposition of lipids in the vascular walls.…”
Section: Rs In Biomedicine and Diagnosticsmentioning
confidence: 79%
“…Results from small-scale studies in samples of 20 to 100 pooled larvae suggest that treating larvae fed on a cholesterol-supplemented diet with statins and/or ezetimibe may prevent the elevated whole-body LDLc and/or total cholesterol levels that are otherwise observed 38,39 . In addition, evidence suggests that treatment with atorvastatin and ezetimibe may reduce vascular lipid deposition 39,73 .…”
Section: Methodsmentioning
confidence: 99%
“…To examine the anti-atherogenic potential of combined treatment with atorvastatin and ezetimibe, we overfed larvae of three backgrounds on a cholesterol-supplemented diet – as described earlier – in the presence or absence of 6μg atorvastatin and 80μg ezetimibe per 1g of dry food 73 from 5 to 9dpf. At 10dpf, larvae were optically screened for atherogenic traits (see ‘ Imaging ’) and used for enzymatic assessment of whole-body lipid and glucose levels (see ‘ Lipid, glucose and protein quantification ’).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, FLIm is useful for quickly measuring lipid to collagen ratios in the fibrous cap , which can provide information about plaque stability. Raman spectroscopy can provide further chemical specificity, and is able to, for instance, distinguish between calcifications, cholesterol or carotenoids . FLIm can create maps of the surface composition at comparable speed with IVUS or OCT whereas Raman spectroscopy is slower and more suitable for point measurements rather than mapping.…”
Section: Introductionmentioning
confidence: 99%